Climate Change and the Future of Indian Organic Agriculture in International Trade - Madrewar, Shivam Satyawan; Khadkikar, Nimisha Ravindra; Katkar, Rohit Chnadrakant; Suryawanshi, Om Vijay; Kapare, Shreya Sharad (MultiTech Publisher, 2024)
This study explores the complex relationship between climate change and Indian organic agriculture, with a particular focus on its implications for international trade.Organic farming in India has witnessed significant growth, driven by increasing consumer demand for organic products both domestically and globally. India, with its diverse agro-climatic conditions, has the potential to be a major player in the global organic market. The paper provides a comprehensive analysis of the current state of organic agriculture in India, including production levels, yield variability, and export performance. It highlights the specific challenges organic farmers face due to climate change, such as water scarcity, soil degradation, and pest and disease pressures, which are exacerbated by climatic fluctuations. Using data from Indian government sources and recent research, the paper presents a detailed assessment of the trends and impacts of climate change on organic farming